Flooding In Taman Universiti, Parit Raja: Causes and Solutions - Wang Siow Zhong; Tan Lai Wai (Recent Trends in Civil Engineering and Built Environment, 2022)
In this study, the main cause of flash flood happened at roadside drain along Taman Universiti Parit Raja, Batu Pahat, Johor is investigated. A series of calculation that had been done using Manning’s equation and Rational method had proved that the high intensity of rainfall is the major cause of flash flood. If there is occurrence of rainfall with intensity more than 4.5 mm/hr happen, then the excessive runoff will flow into the drain and cause overflow of water to occur and then induced the occurrence of flood. Besides that, some other causes such as the irregular constriction of the earth drain flow channel, the growth of grasses and plants in the earth drain, and the topography condition of the study area are also some of the causes of the occurrence of flood at Taman Universiti Parit Raja, Batu Pahat. In addition, the other causes of flooding at the roadside drain of Taman Universiti, Parit Raja is the infiltration rate of soil at the study area. This is because by referring to the research that had been done earlier, it shows the soil type at Parit Raja is silty clay type with low infiltration capacity. Therefore, proper drainage system has to be constructed in order to obstruct the happening of the above scenario and to minimize the damage if the occurrence is bound to happen. Therefore, some possible flood mitigation methods such as the construction of flood wall along both sides of drain, the building of a detention pond and connect the detention pond to the drainage system and to carry out proper channelization and dredging work had been proposed. The peak discharge of the area can be analyzed by using the Hydrologic Modelling System HEC-HMS in order to obtain a precise and accurate result in the future.